2019
DOI: 10.1038/s41598-019-51438-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the dermis zinc transporter ZIP13 promotes the mildness of fibrosarcoma by inhibiting autophagy

Abstract: Fibrosarcoma is a skin tumor that is frequently observed in humans, dogs, and cats. Despite unsightly appearance, studies on fibrosarcoma have not significantly progressed, due to a relatively mild tumor severity and a lower incidence than that of other epithelial tumors. Here, we focused on the role of a recently-found dermis zinc transporter, ZIP13, in fibrosarcoma progression. We generated two transformed cell lines from wild-type and ZIP13-KO mice-derived dermal fibroblasts by stably expressing the Simian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Previous studies have reported that changes in zinc transport proteins were associated with the occurrence of autophagy [ 44 ]. Knockdown of Zip13 in fibroblasts reduced the expression of LC3-I/II and caused severe autophagy defects [ 45 ]. Moreover, inhibition of Zip1 induced mitophagy by reducing mitochondrial membrane potential, suggesting that Zinc transport proteins play crucial roles in regulating autophagy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that changes in zinc transport proteins were associated with the occurrence of autophagy [ 44 ]. Knockdown of Zip13 in fibroblasts reduced the expression of LC3-I/II and caused severe autophagy defects [ 45 ]. Moreover, inhibition of Zip1 induced mitophagy by reducing mitochondrial membrane potential, suggesting that Zinc transport proteins play crucial roles in regulating autophagy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, proteasome inhibitors combined with the inhibition of autophagy induced more human prostate cancer cell death [ 27 ]. The inhibition of autophagy by TPEN (that also chelates zinc) positively affected fibrosarcoma by killing cancer cells selectively [ 28 ]. Similar trends were obtained in our study when HT-1080 cells were cotreated with the compound and CQ, and the decline in cell viability was more significant than in the presence of the compound alone.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al investigated the role of the dermis zinc transporter, ZIP13, in fibrosarcoma progression in dermal fibroblasts obtained from wild-type and ZIP13-KO mice [89]. They observed impairment in autophagy in ZIP13 −/− cells associated with low expression of LC3 at the mRNA and protein levels.…”
Section: Zinc and Autophagymentioning
confidence: 99%